Analisis Kualitas Butir Soal Tes Biologi Menggunakan Rasch Model - Intan Oktaviani; Pramesti Ayu Lestari; Erliana Putri Isnanto; Khalishah Nabilla Putri; Muhammad Ilham Ardiansyah; Suwarto Suwarto (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to analyze the quality of a test instrument using the Rasch model with the assistance of the QUEST software. The analysis was conducted on ten test items developed as a learning evaluation tool. The results showed that only five items received responses from students and could be analyzed quantitatively. These five items demonstrated conformity with the Rasch model, as indicated by INFIT MNSQ values within the acceptable range and OUTFIT t values that met the item fit criteria. The analysis of item difficulty revealed that the instrument contained a range of difficulty levels, including easy, difficult, and very difficult items. However, the item reliability and person reliability values were classified as low, indicating that the consistency of the instrument and the stability of the measurement results were not yet optimal. In addition, several items did not function properly because they did not receive any student responses and therefore lacked empirical validity. Based on these findings, it can be concluded that the developed test instrument does not yet fully meet the criteria of a high-quality learning evaluation tool and still requires improvement, particularly in terms of item quality and instrument reliability.